Economics and Ageing Volume III: Long-term Care and Finance - Iparraguirre, José Luis. (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This upper level textbook provides a coherent introduction to the economic implications of individual and population ageing. Placing economic considerations into a wider social sciences context, this is ideal reading not only for advanced undergraduate and masters students in health economics and economics of ageing, but policy makers, professionals and practitioners in gerontology, sociology, health-related sciences, and social care. This volume introduces topics in labour economics, including the economic implications of ageing workforces. It covers pension economics and pension systems with their macroeconomic and distributive effects, and the question of risk. Finally, it describes macroeconomic consequences of ageing populations on aggregate saving, inflation, international trade, and financial markets.